STARK WIDTHS OF Sc IV SPECTRAL LINES WITHIN 4s-4p TRANSITION ARRAY - Dimitrijević, Milan S. (Bulletin of Natural Sciences Research, 2017)
Stark full widths at half maximum of six 4s-4p Sc IV spectral lines, broadened by collisions with electrons, have been calculated for electron density of 1017 cm-3 by using the modified semiempirical method. The results are provided for temperatures from 10 000 K to 160 000 K. They are used also to discuss the similarities of Sc IV spectral lines within multiplet, supermultiplet and transition array. Obtained results will be included in the STARK-B database which is also a part of Virtual atomic and molecular data center (VAMDC).